Industrial training system / Muhammad Afiq Muhamad Yusof - Muhamad Yusof, Muhammad Afiq (2013)
Industrial Training System for Faculty of Computer Science and Mathematics (FSKM) is based on the latest technology where management of Industrial Training becomes easier, faster and more efficient. It probably is a complete system for use by administrators, students, companies and supervisors to help FSKM in managing students undergoing industrial training system. In this system, flexible features can support multiple users allowing them to apply for industrial training through this system. Waterfall model is used in order to help developing this system. Waterfall model has five phases which consists of requirement, design, implementation, verification and documentation. This system is designed as a web-based system for which the benefits are accessible from anywhere and anytime. It has been developed using PHP as the primary languages while the languages such as XML and HTML are also used as a complement to the perfection of the system. The Industrial Training System has been tested in FSKM UiTM Terengganu. The result of this proposed system is evaluated based on the user interface, usability and functionality using a set of questionnaire. The result has shown 80% positive feedback about this system. As a conclusion, it is hoped this system can solve or reduce the problems encountered previously by members of FSKM